Knowledge management enablers and knowledge management implementation - Mohamed Razi, Mohamed Jalaldeen; Nor Shahriza, Abdul Karim; Norshidah, Mohamed (2012)
The importance of Knowledge Management (KM) process implementation for business success is well accepted. Evaluation of organizational members’ intention toward KM and the factors that influence on their intentions are considered important for KM success. Thus, this work attempts to correctly define the variables that can be used to measure intention towards KM and the influencing factors on intention through factor analysis. The analysis was done using data collected from 313 executives in the Sri Lankan telecommunication industry.